Al-Qur'an and the Da'wah Approach Model in the Disruption Era - Aftonur Rosyad; Eko Zulfikar (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Da'wah is part of the commands of the Qur'an. Many of the several verses of the Qur'an describe the concept of da'wah. With the development of the era, the method or approach of da'wah must be able to reach the reality on the ground. The concept of da'wah brought by the Walisongo is certainly different in terms of approach, culture, society and strategy. In the QS. al-Nahl verse 125, it is explained about several methods of da'wah, namely wisdom, mauidzah hasanah and mujadalah. By using qualitative methods and content analysis, this article concludes that the da'wah approach in navigating the era of disruption can use the Walisongo's footsteps, namely the theological approach, scientific approach, institutional approach, social approach, cultural approach, structural approach, and economic approach. From these several approaches, da'i can pick and choose from the several approaches above to serve as a way of preaching in the era of disruption.